A comparative study on the photodegradation of methyl orange, methylene blue u sing Fe2O3, Mn2O3, and Fe2O3 – Mn2O3 nanomaterials - Nguyen Vu Ngoc Mai; Le Bao Hung; Pham Ngoc Chuc; Duong Thi Lim and Dao Ngoc Nhiem; Nguyen Quang Bac; Tran Dai Lam (My University, 2022)
A comparative study on the photodegradation of methyl orange, methylene blue u sing Fe2O3, Mn2O3, and Fe2O3 – Mn2O3 nanomaterials
Keywords: Fe2O3 - Mn2O3